PENGARUH KEBIJAKAN PEMASARAN GULA TERHADAP PENAWARAN DAN HARGA DOMESTIK GULA INDONESIA - Isti Widhaningsih (Agro Ekonomi, 2010)
Marketing of sugar cane in three periods 1971-2005 ( Bulog, free trade and import controls ) has received government intervention especially on supply and domestic prices. The purpose of this research is to find out influencing factors on supply, production, imports and domestic price of sugar cane and its trend in the future. Descriptive analysis is used as well as autoregressive model (ARI) and trend analysis. The result showed that the area’s sugar cane crop has high contribution to the production and supply of sugar cane in Indonesia. Sugar imports are influenced by the marketing policy of tree trade and import control period, the gap between consumption and production. Domestic production and exchange rates influenced domestic of sugar in the period of Bulog and import controls. Sugar marketing policy did not influence the effectiveness of production and supply of cane sugar in Indonesia. Import control period had a positive effect for domestic prices, yet have not managed the amount of sugar imports. In addition to price and tariff policy to protect the cane sugar producers in the country, it can be realized by on farm increasing intensification and extension as well as further optimization of the sugar factory.